Gas Storage Model of Residual Coal Adsorption in Abandoned Mine - San Zhao; Xiangjun Chen; Lin Wang; Lin Li (Adsorption Science & Technology)
Due to the insufficient accurate evaluation model of gas resources in abandoned mines, the development and utilization of abandoned mine gas resources in China are still in the preliminary exploration stage. To this end, in response to the problem of imprecise assessment of gas resource reserves in the adsorbed state of residual coal, the No. 3 coal seam in Jincheng mine was used as the research object, by analyzing the evolution of the ambient gas pressure and temperature of the residual coal in the abandoned mine, and simulating the pressure and temperature environment in which the residual coal is located, the gas adsorption experiment of the residual coal was carried out in this environment, and a gas storage model of the residual coal was constructed with the combination of the adsorption theory. The results show that pressure has a positive effect on gas adsorption by residual coal, while temperature has a negative effect on it. The adsorption potential gradually decreases with increasing pressure and increases with increasing temperature, while the adsorption space increases with increasing pressure and decreases with increasing temperature. The adsorption characteristic curves obtained by the two methods are temperature independent and polynomial in shape, and the fitted correlation coefficient of method 1 is generally higher than that of method 2. The adsorption characteristic curves of two methods are best fitted at k=2.5, so the value of k is most appropriately taken as 2.5 when calculating the virtual saturation vapour pressure. The average relative errors between the predicted and measured values of method 1 and 2 were 2.98% and 7.13%, respectively. The prediction effect of method 1 was significantly better than that of method 2 and met the requirements of engineering applications; therefore, method 1 was used to establish a model for the adsorbed gas storage capacity of residual coal in abandoned mines.